Cultivating Moderate Islamic Education and Anti-Discrimination Values in Pesantren: An Ethnographic Study - Sulton, Ahmad; Sunandito, Virgiawan Eko (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the role of Pesantren Darul Huda Mayak Tonatan Ponorogo as an institutional agent of moderate and anti-discrimination Islamic education in strengthening social harmony. Prior scholarship has tended to examine religious moderation and anti-discrimination education in Islamic boarding schools as discrete phenomena, overlooking the integrated socio-pedagogical dynamics through which these values are systematically internalized. Employing a qualitative ethnographic design, data were collected over 12 months through participatory observation, semi-structured in-depth interviews, and documentary analysis involving 46 purposively and snowball-sampled key informants comprising one senior kyai, ten teachers and ustaz, twenty santri, and fifteen influential alumni. Data were analyzed using Miles et al.'s (2014) interactive model, encompassing data condensation, data display, and conclusion drawing/verification. Validity was established through source, method, and theoretical triangulation, supplemented by member checking. Findings reveal three principal thematic domains. First, moderation and anti-discrimination values are internalized through the formal curriculum of classical Islamic texts, the hidden curriculum of religious traditions and communal practices, exemplary kyai moral conduct, and the egalitarian social environment of pesantren life. Second, the pesantren strengthens social harmony through its functions as a social integration agent, community conflict mediator, builder of multi-dimensional social capital, and agent of cultural moderation. Third, the dialectical interplay between leadership, institutional value structure, and santri agency – analyzed through Giddens's structuration theory – continuously reproduces and transforms moderation values to remain contextually relevant. This study advances a pesantren-based educational model integrating moderation and anti-discrimination values through curriculum, tradition, exemplary leadership, and community engagement, providing conceptual and empirical foundations for national education policies oriented towards tolerance, social justice, and sustainable social harmony in multicultural societies.